Islamic rural bank mission drift: Equity financing vs debt-based financing - Afriadi, Fiqih; Pranoto, Pranoto; Kurniawaty, Erlita; Zamzami, R. Mohd. (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – This study aims to compare the depth of outreach, financial performance, and trade-off between the depth of outreach and financial performance (mission drift) between equity financing and debt-based financing in Indonesian Islamic Rural Banks.Methodology – We compare the depth of outreach and financial performance using descriptive statistics and explore mission drift comparisons using OLS time series. Findings – The depth of the outreach comparison shows that debt-based financing performs better. However, equity financing outperforms financial performance. The regression results show mission drift in Musharaka and Multiservice financing, indicating that both sides have mission drift. However, there is no mission drift in Murabaha financing, which constitutes the majority of financing in Indonesian Islamic Rural Banks. Murabaha financing synchronously demonstrates excellent depth of outreach and financial performance.Implications – Islamic Rural Banks in Indonesia need product innovation in equity financing to obtain a better depth of outreach and avoid mission drift. The simplicity of the practice in Murabaha can be a reference for product innovation in Islamic Rural Banks, while the government can support Indonesian Islamic Rural Banks' product innovation by providing appropriate regulations.Originality – This study seeks to fill the comparison gap between mission drifts in Indonesian Islamic rural bank financing. There is a limitation in studies of Islamic rural bank financing mission drifts in Indonesia since the comparison of mission drift deals only with Islamic microfinance at a global level.